Genetic Diversity of Dacrycarpus imbricatus At Bukit Tapak, Tabanan, Bali Based on RAPD Marker - Made Pharmawati; I Made Anom Sutrisna Wijaya (Biotropika: Journal of Tropical Biology, 2021)
Dacrycarpus imbricatus Blume is a member of the Podocarpaceae family. In Bali, D. imbricatus was found in Bukit Tapak, Tabanan Regency. This species is one of the dominant species in Bukit Tapak. This study aimed to determine the genetic variation of D. imbricatus in Bukit Tapak using molecular markers RAPD (Random Amplified Polymorphic DNA). The genetic diversity of D. imbricatus needs to be studied to obtain the information used for the conservation of this species. Leaf samples were taken from Bukit Tapak, Candikuning, Baturiti, Tabanan Regency, Bali. DNA was extracted using the CTAB method, followed by extraction using chloroform: isoamyl alcohol. DNA precipitation was carried out using ethanol. RAPD analysis was performed using polymerase chain reaction (PCR) using four primers. PCR products were visualized using agarose gel electrophoresis and ethidium bromide staining. The results showed that the amplified DNA bands ranged from 1 to 5 bands with DNA band sizes ranging from 230 bp - 422 bp. Only OPA4 and UBC106 primers can be used to detect D. imbricatus diversity based on the H, D, and R values. The detected genetic variation is low, as indicated by an average polymorphism of 32.5% and similarities between samples ranging from 0.51 to 1